Botulinum toxin A–induced paralysis of the lateral abdominal wall after damage-control laparotomy: A multi-institutional, prospective, randomized, placebo-controlled pilot study. Issue 2 (February 2016) - Zielinski, Martin D.; Kuntz, Melissa; Zhang, Xiaoming; Zagar, Abigail E.; Khasawneh, Mohammad A.; Zendejas, Benjamin; Polites, Stephanie F.; Ferrara, Michael; Harmsen, William Scott; Ballman, Karla S.; Park, Myung S.; Schiller, Henry J.; et al.
Abstract : BACKGROUND: Damage-control laparotomy (DCL) is a lifesaving operation used in critically ill patients; however, interval primary fascial closure remains a challenge. We hypothesized that flaccid paralysis of the lateral abdominal wall musculature induced by botulinum toxin A (BTX) would improve rates of primary fascial closure, decrease duration of hospital stay, and enhance pain control. METHODS: Consenting adults who had undergone a DCL at two institutions were prospectively randomized to receive ultrasound-guided injections of their external oblique, internal oblique, and transversus abdominus muscles with either BTX (150 mL, 2 U/mL) or placebo (150-mL 0.9% NaCl). Patients were excluded if they had a body mass index of greater than 50, remained unstable or coagulopathic, were home O2 dependent, or had an existing neuromuscular disorder. Outcomes were assessed in a double-blinded manner. Univariate and Kaplan-Meier estimates of cumulative probability of abdominal closure were performed. RESULTS: We randomized 46 patients (24 BTX, 22 placebo). There were no significant differences in demographics, comorbidities, and physiologic status. Injections were performed on average 1.8 ± 2.8 days (range, 0–14 days) after DCL. The 10-day cumulative probability of primary fascial closure was similar between groups: 96% for BTX (95% confidence interval [CI], 72–99%) and 93% for placebo (95% CI, 61–99%) (HR, 1.0; 95% CI, 0.5–1.8). No difference between BTX and placebo groups was observed for hospital length of stay (37 days vs. 26 days, p = 0.30) or intensive care unit length of stay (17 days vs. 11 days, p = 0.27). There was no difference in median morphine equivalents following DCL. The overall complication rate was similar (63% vs. 68%, p = 0.69), with two deaths in the placebo group and none in the BTX group. No BTX or injection procedure complications were observed. CONCLUSION: The use of BTX after DCL was safe but did not seem to affect primary fascial closure, hospital length of stay, or pain modulation after DCL. Given higher-than-expected rates of primary fascial closure, Type II error may have occurred. LEVEL OF EVIDENCE: Therapeutic study, level III.